Morals and the Beautiful in N. Hartmann’s philosophy - Juršėnas, Nikodemas (Problemos, 1972)
The article deals with a critical analysis of the problem of interdependence between moral and aesthetic values. The conceptions of values, their specific character, their relations to the values of the good and to business-like cooperation, are discussed first. At the same time the general methodological conception of “critical ontology”, its failure in solving the main spiritual problems of man as well as some positive features of this philosophy, are touched upon. The second part of the article is dedicated to a consideration of the structure of the beautiful, its relations to moral values, as well as to the values of the good and to business-like cooperation.